Straits settlements laws [1876-1935] (Petaling Jaya : Arkib Negara)
Mengandungi Vol. IV no. 197-207. Vol. V no. 208-239. Vol. 1 edition of 1936 hapter 1-41. Vol. II (Chapter 42-44 termasuk ordinance no. 198 Fraudulent Debtors (Ord. XVI of 1923); Ordinance no. 199 Volunteer Force (XXX of 1921; Ord. XXXVIII of 1922; Ord. XXIV of 1923); Ordinance no 200 cinematograph films (IV of 1924); Ord. no. 208 Presbyterian Church (Ord. II of 1876); Ordinance no. 210 Raffles Soceities (Ord. VII of 1878); Ordinance no. 211 Tan Tock Seng's Hospital (Ord. VII of 1880); Ord. no. 212 Hong Kong and Shanghai Bank (ore. X of 1881); Ordinance no. 220 Sultan Hussain (Ord. XIII of 1904); Ordinance no. 224 King Edward VII College of Medicine (Ord. XV of 1905; Ord. XXXIX of 1921).